Genetic background influences adaptation to cardiac hypertrophy and Ca2+ handling gene expression - Waters, Steve B.; Diak, Doug; Zuckerman, Matthew; Leoni, Lara; Goldspink, Paul H.; Roman, Brian B. (Frontiers in Physiology, 2013)
Genetic variability has a profound effect on the development of cardiac hypertrophy in response to stress. Consequently, using a variety of inbred mouse strains with known genetic profiles may be powerful models for studying the response to cardiovascular stress. To explore this approach we looked at male C57BL/6J and 129/SvJ mice. Hemodynamic analyses of left ventricular pressures indicated significant differences in 129/SvJ and C57BL/6J mice that implied altered Ca2+ handling. Specifically, 129/SvJ mice demonstrated reduced rates of relaxation and insensitivity to dobutamine(Db). We hypothesized that altered expression of genes controlling the influx and efflux of Ca2+ from the sarcoplasmic reticulum was responsible and investigated the expression of several genes involved in maintaining the intracellular and sarcoluminal Ca2+ concentration using quantitative real-time PCR analyses (qRT-PCR). We observed significant differences in baseline gene expression as well as different responses in expression to isoproterenol (ISO) challenge. In untreated control animals, 129/SvJ mice expressed 1.68x more ryanodine recptor 2(Ryr2) mRNA than C57BL/6J mice but only 0.37x as much calsequestrin 2(Casq2). After treatment with ISO, sarco(endo)plasmic reticulum Ca2+-ATPase(Serca2) expression was reduced nearly two-fold in 129/SvJ while expression in C57BL/6J was stable. Interestingly, β(1) adrenergic receptor(Adrb1) expression was lower in 129/SvJ compared to C57BL/6J at baseline and lower in both strains after treatment. Metabolically, the brain isoform of creatine kinase(Ckb) was up-regulated in response to ISO in C57BL/6J but not in 129/SvJ. These data suggest that the two strains of mice regulate Ca2+ homeostasis via different mechanisms and may be useful in developing personalized therapies in human patients.